A study of platelet to lymphocyte ratio in patients with metabolic syndrome - ., Thyagaraj; Mohan, Manjushree; ., Sreedevi (International Journal of Advances in Medicine, 2020)
Background: The prevalence of the metabolic syndrome varies around the world, in part reflecting the age and ethnicity of the populations studied and the diagnostic criteria applied. Numerous studies have shown an association of Metabolic Syndrome (MS) and insulin resistance (IR) with inflammation. Platelet-lymphocyte ratio (PLR) has recently emerged as a novel inflammatory index that may serve as an important predictor of inflammatory state and overall mortality. Aim of this study is to evaluate the PLR in patients with MS and to correlate the same with the severity of MS based on its categories. Methods: A cross sectional study was conducted on 210 subjects (105 subjects with Metabolic Syndrome and 105 age and gender matched control participants without Metabolic Syndrome) seen on outpatient basis at hospitals attached to Basaveshwara medical college and research institute, Chitradurga. Detailed history including history of risk factors if any, physical examinations and baseline investigations like complete blood counts, HbA1c levels, serum glucose levels, fasting lipid profile, electrocardiography and the data was analyzed using appropriate statistical methods. Results: PLR was 6% higher in males (PLR-144.77±34.6) when compared to females (PLR-136.57±30.4) in subjects with metabolic syndrome. There was 95.9% higher PLR in subjects with metabolic syndrome when compared to subjects without metabolic syndrome (p<0.05). Furthermore, PLR increased more as severity of metabolic syndrome increased (5/5 PLR-180.55±25.3,4/5 PLR-132.33±23.6, 3/5 PLR- 109.63±22.6 and non-metabolic syndrome (PLR- 77.45±19.5). Conclusions: In this study, PLR above 90 predicted significant inflammation. PLR is calculated from complete blood count with differential, is an inexpensive, easy to obtain, widely available marker of inflammation, which can aid in the risk stratification of patients with various cardiovascular diseases in addition to the traditionally used markers.